A Comparative Evaluation of Shear Bond Strength of Creation Ceramic Veneer to Metal and Zirconia Cores - E Jalalian; S Shiari; SH Jalalian; M Mirzakhani (Islamic Azad University, 2020)
Abstract Background and Aim: High chipping rates of the veneering porcelain of zirconia ceramic restorations have been reported in clinical studies. Thus, the shear bond strength (SBS) between the zirconia core and veneering porcelain requires investigation. Materials and Methods: In this in-vitro study, at first, using a computer-aided design/computer-aided manufacturing (CAD/CAM) machine, 16 zirconia cores of Kerox were provided. Using the casting method, 16 base metal cores were provided. All the cores were veneered with the Creation ceramic veneer. Afterwards, the samples were put under a static force in the universal testing machine at a crosshead speed of 1 mm/minute until fracture. T-test was used to analyze the data. Results: The mean SBS for the base metal and zirconia groups was 27±7.43 and 27.75±8.75 Megapascal (MPa), respectively (P=0.812). Conclusion: There was no significant difference between the metal-ceramic and zirconia ceramic groups in SBS so that the Creation ceramic veneer may solve the problems related to the bond of all-ceramics to ceramic veneers.